Generating extremely large-volume reionization simulations. Issue 4 (8th September 2022) - Greig, Bradley; Wyithe, J Stuart B; Murray, Steven G; Mutch, Simon J; Trott, Cathryn M
ABSTRACT: Preparing for a first detection of the 21-cm signal during reionization by large-scale interferometer experiments requires rigorous testing of the data analysis and reduction pipelines. Validating that these do not erroneously add/remove features mimicking the signal (e.g. from side lobes or large-scale power leakage) requires simulations extending beyond the primary field of view. However, the Murchison Wide Field Array (MWA) with a field of view of ∼25 2 deg 2 would require simulations spanning several Gpcs, which are currently infeasible. To address this, we developed a simplified version of the seminumerical reionization simulation code 21cmfast, sacrificing some physical accuracy (linear structure formation) in favour of extremely large volumes. We then constructed a 7.5 Gpc comoving volume specifically tailored to the binned spectral resolution of the MWA (∼1.17 cMpc), required for validating the pipeline used in the 2020 MWA 21-cm power spectrum (PS) upper limits. With this large-volume simulation, we then explored: (i) whether smaller volume simulations are biased by missing large-scale modes, (ii) non-Gaussianity in the cosmic variance uncertainty, (iii) biases in the recovered 21-cm PS following foreground wedge avoidance, and (iv) the impact of tiling smaller simulations to achieve large volumes. We found (i) no biases from missing large-scale power, (ii) significant contribution from non-Gaussianity, as expected, (iii) a 10–20 per cent overestimate of the 21-cm PS following wedge mode excision, and (iv) tiling smaller simulations underestimates the large-scale power and cosmic variance.